THE INFLUENCE OF MOTIVATION TO PHYSICS LEARNING ACHIEVEMENTS GRADE XI MIA STUDENTS OF SMA MUHAMMADIYAH 2 SURABAYA - CHABIBUR ROCHMAN ALWACHIDY, MUCHAMMAD; , SUPARDIYONO (Inovasi Pendidikan Fisika, 2018)
This research aims to described the influence of learning motivation to physics learning achievements grade XI MIA Students of SMA Muhammadiyah 2 Surabaya. The type of research is non experiment. The subject of research uses 185 students of XI science classes. This research method used is test and questionnaire with the questionnare sheets and physics learning achievemets tests. The questionnare analyze with factor analyze KMO and Bartlett?s Test of sphericity and for the data used normality test, linearity test, simple regression linearity test, coefficient product moment correlation (R) and coefficient determination (R square). The results of the research show the motivation questionnare is significant with coefficience KMO value 0,779 and bartlett?s test significant (x^2=1664,161, df = 231, p < 0,000) with six factor loading cumulative variance 57,647%. For the result, simple regression linear test show that motivation influenced to physics learning achievement 38,4% expressed the regression equation that is Y = -10,811+0,381x with coefficient product moment correlation R value 0.619 includes having a high level of relationship between motivation and physics learning achievement